Peran Keluarga Dengan Kepatuhan Minum Obat Pasien Skizofrenia - Ariyanto; Ardhiles Wahyu Kurniawan; Apriyani Puji Hastuti (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Schizophrenia is a chronic mental disorder that requires long-term treatment and high medication adherence to prevent relapse. However, non-adherence to medication among patients with schizophrenia remains a major problem, particularly after patients return to the family environment. As the closest support system, families play an important role in supervising, motivating, and assisting patients to adhere to medication regimens. This study aimed to analyze the relationship between family role and medication adherence among patients with schizophrenia at Sofifi Mental Hospital, North Maluku. This study employed a quantitative correlational design with a cross-sectional approach. The study population consisted of families of patients with schizophrenia at Sofifi Mental Hospital, with a sample of 60 respondents selected using accidental sampling. Data were collected using a family role questionnaire as a medication supervisor and the Morisky Medication Adherence Scale (MMAS-8). Data analysis was conducted using descriptive statistics and inferential analysis with the Spearman Rank correlation test. The results showed that most families had a moderate to good level of family role, with a mean score of 26.4 ± 5.8. Medication adherence among patients was categorized as moderate, with a mean score of 6.1 ± 1.7. The Spearman Rank test indicated a significant and positive relationship between family role and medication adherence among patients with schizophrenia (r = 0.56; p-value = 0.001). These findings indicate that better family involvement in providing support, supervision, and emotional control is associated with higher medication adherence among patients with schizophrenia. Therefore, family-based mental health nursing interventions should be optimized to enhance medication adherence and reduce relapse rates among patients with schizophrenia